Cinema 2 - "Deleuze, Gilles" (London, 2005)
Offers a fascinating analysis of the representation of time in film and the cinematic treatment of memory, thought and speech, and looks at the work of Godard, Hitchcock and Welles.
Keywords: Social psychology